Employability skills required of accountants - Tan, Lin Mei; Fawzi, Laswad (2017)
Employability skills have become increasingly important in a competitive job market in a globalised world of advanced technology.Our study examines employability skills of accountants as indicated in job advertisements in Australia and New Zealand, as they provide a window into the skills that are most valued by employers.The results show that of the 31 identified skills, 13 were most cited.Importantly, the most sought after skills included the ability to collaborate with colleagues, present, discuss and defend views, and having a positive attitude.Overall, a team player with a positive attitude and good communication skills appeared to be the most valued behavioural skill as perceived by employers.This probably reflects a change in the work of accountants, from being ‘backroom number crunchers’ to engaged business professionals.